2021
DOI: 10.2174/1573396317666210222115321
|View full text |Cite
|
Sign up to set email alerts
|

The Fluctuations of Melatonin and Copeptin Levels in Blood Serum During Surgical Stress Regarding the Pediatric Population

Abstract: Introduction: Copeptin is known to be associated with heart damage, while melatonin is a regulatory hormone associated with circadian rhythm and represents the levels of inflammation in the body. Methods and patients: The aim of the study was to measure in different surgeries the levels of copeptin and melatonin at different times before and after surgery in 56 patients aged from 5 days to 13.6 years. We measured copeptin in 50-microL serum and plasma samples from patients before surgery, immediately after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Alterations in plasma levels of melatonin, due to surgical stress, have been also demonstrated in the pediatric population [ 22 ] with a reduction in melatonin values in the postoperative time, at 24 h, that was significantly higher in patients aged between 3 and 6 years of age compared with patients at 6–12 year of age. The difference between neonatal and pediatric patients may be due to the irregular secretion of melatonin in the first years of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in plasma levels of melatonin, due to surgical stress, have been also demonstrated in the pediatric population [ 22 ] with a reduction in melatonin values in the postoperative time, at 24 h, that was significantly higher in patients aged between 3 and 6 years of age compared with patients at 6–12 year of age. The difference between neonatal and pediatric patients may be due to the irregular secretion of melatonin in the first years of life.…”
Section: Discussionmentioning
confidence: 99%
“…A multifactorial analysis in the paper by Dragoumi et al revealed a statistically significant difference between 24 h postoperative melatonin values in age groups three (3–6 years) and five (6–12 years old). Age group three (3–6 years) showed significantly lower postoperative melatonin values compared with age group five (6–12 years) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%